Modifying the traditional plough - maresha - for better management of Vertisols - Astatke, A.; Kelemu, F. (International Livestock Centre for Africa, 1993)
This chapter provides a brief description of relevant farmers' practices, the traditional implements used and the experience of the Joint Vertisols Project (1986-91) in developing simple and low-cost implements for Vertisols in a highland agricultural system.